Influence Digital Marketing Technology And Brand Image On The Purchase Decision Of Ms Glow In Students Of Universitas Asa Indonesia - Nirmala, Yanti (Cattleya Darmaya Fortuna, 2023)
Looking beautiful and attractive is a demand for DIII Hospitality students of ASA University. Indonesian. Beauty products that are widely circulated today can support their appearance. M.S Glow products are one of the products that are familiar to the public. Most female students at this university use this brand of products. In addition information can be easily obtained through social media, prices and easy to find on official agents who sell it. This Descriptive quantitative research analyzes separately and simultaneously the influence of digital marketing variables and brand image variables on the purchase decision of M.S Glow products to ASA Indonesia University students majoring in DIII Hospitality using SPSS 20 as the data processor. This study used 85 respondents consisting of female students only. The results of the study found that the use of digital marketing as a promotion and brand image influenced the purchase decision of M.S Glow products. If the variables of digital marketing and brand image increase, it will certainly affect the increase in purchasing decisions for students of this university.